1958
DOI: 10.1099/00221287-18-3-543
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitors and their Antagonists as Mutagens and Antimutagens in Escherichia coli

Abstract: Thirty-five substituted benzimidazoles, benzotriazoles and quinoxalines were tested as growth inhibitors on three mutants of Escherichia coli, strain W, having different purine requirements and on the ciliate Tetrahymena geleii. A number of the compounds, especially those with a nitro group in the benzene ring, were inhibitory. Both organisms were affected in a similar way by the compounds. Several of these analogues were tested for mutagenic activity a t the purine and streptomycin loci in a purine-requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1959
1959
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is conceivable that these differences in cell treatment might alter the incorporation of the analogue. Greer (1958) observed that 250 Ag/ml had on effect on the growth rate or the spontaneous mutation rate from auxotrophy to prototrophy in E. coli. Witkin (1958), however, postulated that the increased mutagenesis was due to an inhibition of DNA synthesis by caffeine, allowing more time for "promutants" to become mutants before the start of DNA synthesis.…”
Section: Discussionmentioning
confidence: 95%
“…It is conceivable that these differences in cell treatment might alter the incorporation of the analogue. Greer (1958) observed that 250 Ag/ml had on effect on the growth rate or the spontaneous mutation rate from auxotrophy to prototrophy in E. coli. Witkin (1958), however, postulated that the increased mutagenesis was due to an inhibition of DNA synthesis by caffeine, allowing more time for "promutants" to become mutants before the start of DNA synthesis.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is still a possibility that effective and versatile anticancer drugs may be finally discovered as examples of the mutagen-antimutagen relationship. In fact, some mutagens are counteracted by structurally analogous agents as seen in caffeine and theophylline versus adenosine and guanosine (92), and 4-nitro-6-hydroxybenzimidazole versus 4-hydroxy-6-nitrobenzotriazole (33). Furthermore, the "counteractive interference" between some mutagens for bacteria as well as some RD inducers for yeast (see Section IV-C) makes the prospect somewhat brighter.…”
Section: Cancer and The Rd Mutationmentioning
confidence: 99%
“…Since caffeine is a universal beverage and is consumed in large quantities by the human race, its effect during gestation on the developing offspring is important. There is good evidence that caffeine is mutagenic in bacteria (Demerec and his co-authors, 1950;Demerec, Bertani & Flint, 1951;Gezelius & Fries, 1952;Novick, 1955;Greer, 1968), fungi (Fries, 1950;Zetterberg, 1959) and plants (Kihlman & Levan, 1949;Kihlman, 1952), as well as in Drosophila (Andrew, 1959;Ostertag, 1963;Ostertag & Haake, 1966;Mittler, Mittler & Owens, 1967) and in human cells in vitro (Ostertag, Duisberg & Stürmann, 1965;Ostertag, 1966a, b;Ostertag & Greif, 1967). Although there have been some conflicting reports on the mutagenicity of caffeine in higher organisms (Adler, 1970;Epstein, 1970), chromosomal breakage has been induced in human cell cultures as well as in Drosophila (Kuhlmann, Fromme, Heege & Ostertag, 1968).…”
Section: Introductionmentioning
confidence: 99%